Evaluation of high oil residue camelina meal (HORM) on Atlantic salmon (Salmo salar) growth performance, carcass composition, intestinal morphology and inflammatory biomarker gene expression. (18th November 2021) - Collins, Stephanie A.; Han, Chenxin; Xue, Xi; Brown, Tyler D.; Rise, Matthew L.; Tobin‐Huxley, Gillian; Colombo, Stefanie M.; Anderson, Derek M.
Abstract: High oil residue camelina meal (HORM) was included in low fish meal, low fish oil diets for juvenile Atlantic salmon at a dietary inclusion level of 0, 20, 40, 60, 80 or 100 g/kg to determine the effect of diet on growth performance, carcass composition, morphology and inflammatory biomarker gene expression in the distal intestine. Diets were fed to Atlantic salmon (mean weight ± standard deviation: 2.3 ± 0.1 g/fish; 50 fish/40 L tank; 3 tanks/treatment) for 16 weeks. Salmon fed 0, 20 and 40 g/kg HORM had significantly higher weight gain, growth rate, protein efficiency, and lower feed conversion ratio, than salmon fed 60, 80 and 100 g/kg HORM. Distal intestinal morphology showed lamina propria were wider in salmon fed 60 g/kg HORM, compared with salmon fed the other dietary treatments. Transcript expression of the distal intestine showed significant differential expression across treatments, as determined by qPCR. IL17Ar and GILT1 were down‐regulated 1.3‐ to 1.5‐fold in salmon fed 80 and 100 g/kg HORM, compared with 0 g/kg HORM. Nfkb2 was also down‐regulated in salmon fed 40, 80 and 100 g/kg HORM, compared with the control treatment. The transcript encoding thioredoxin was 1.9‐fold upregulated in salmon fed 100 g/kg HORM compared with 0, 20 and 40 g/kg HORM‐fed groups. This study finds that inclusion of dietary HORM at 20 and 40 g/kg results in acceptable growth. In general, transcript expression of some inflammation‐relevant genes responded to dietary HORM; however, further research is needed to determine whether the higher levels of HORM (≥60 g/kg) are associated with inflammation and detrimental to fish health.